(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2021)
The research deals with the image in the Umayyad poetry and how these images embodied the Islamic spirit and how Islam influenced it. The inclusion of images in several topics and areas of the Umayyad poetry whether these topics were concerned with the traditional topics of the Arabic poetry that exist in the Pre- Islamic and Islamic poetry or the topics that clearly appeared in such literature such as polite love, political, religious sects and parties. I’ll point out some samples of the Umayyad poetry with the Islamic image and the objectives of poetry and how these images can illustrate the content of the poem that implies the meaning of the poem and its meaning.